THE POTENTIAL OF MATURE PANDAN LEAVES AS A SOURCE OF CHLOROPHYLL FOR NATURAL FOOD COLORANTS - Chatarina Lilis Suryani Suryani; Tutik Dwi Wahyuningsih; Supriyadi Supriyadi; Umar Santoso (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Plant leaves are the primary source of natural colorants for food, mainly due to their chlorophyll content. However, the plant types and the degree of leaf maturity determine the quality and quantity of the chlorophyll. This study aimed to determine the best maturity level of pandan (Pandanus amaryllifolius Roxb.) leaves that serves as potential source of chlorophyll for natural food colorants. Eighty three pandan plants obtained from six different farming locations in Bantul Regency, Yogyakarta, Indonesia were used as samples. The leaves were grouped into four levels of maturity using descriptive statistics based on their morphology, anatomy, color, and chlorophyll contents. The results showed that the average number of leaves ranged from 20-24 leaves per plant (at 95% confidence interval), and 96.4% of the plant had a maximum of 24 leaves. The leaf maturity was grouped into (1) young, (2) medium, (3) mature, and (4) over mature, corresponding to leaf number 1-6, 7-12, 13-18, and 19-24, respectively. The higher the leaf maturity, the higher the chlorophyll content. However, the over mature leaves were only slightly different from the mature ones. In addition, pandan leaves have specific flavor and contain carotenoid, phenolic, and flavonoid substances. Anatomically, the mesophyll’s size was greatest in the mature leaves, while the size of chloroplast was not significantly different from medium to over mature leaves. Based on the chlorophyll content and mesophyll size, it was concluded that mature pandan leaves were the best source of chlorophyll, containing chlorophyll of 623.08 mg/100 g dry weight (DW).